A novel splice-site mutation in angiotensin I-converting enzyme (ACE) gene, c.3691+1G>A (IVS25+1G>A), causes a dramatic increase in circulating ACE through deletion of the transmembrane anchor. - Alexandre Persu (Public Library of Science (PLoS), 2013)
Background Angiotensin-converting enzyme (ACE) (EC 4.15.1) metabolizes many biologically active peptides and plays a key role in blood pressure regulation and vascular remodeling. Elevated ACE levels are associated with different cardiovascular and respiratory diseases. Methods and results Two Belgian families with a 8-16-fold increase in blood ACE level were incidentally identified. A novel heterozygous splice site mutation of intron 25 - IVS25+1G>A (c.3691+1G>A) - cosegregating with elevated plasma ACE was identified in both pedigrees. Messenger RNA analysis revealed that the mutation led to the retention of intron 25 and Premature Termination Codon generation. Subjects harboring the mutation were mostly normotensive, had no left ventricular hypertrophy or cardiovascular disease. The levels of renin-angiotensin-aldosterone system components in the mutated cases and wild-type controls were similar, both at baseline and after 50 mg captopril. Compared with non-affected members, quantification of ACE surface expression and shedding using flow cytometry assay of dendritic cells derived from peripheral blood monocytes of affected members, demonstrated a 50% decrease and 3-fold increase, respectively. Together with a dramatic increase in circulating ACE levels, these findings argue in favor of deletion of transmembrane anchor, leading to direct secretion of ACE out of cells. Conclusions We describe a novel mutation of the ACE gene associated with a major familial elevation of circulating ACE, without evidence of activation of the renin-angiotensin system, target organ damage or cardiovascular complications. These data are consistent with the hypothesis that membrane-bound ACE, rather than circulating ACE, is responsible for Angiotensin II generation and its cardiovascular consequences.